An intrastrand d(GpG) platinum crosslink in duplex M13 DNA is refractory to repair by human cell extracts. - Szymkowski, D E (1992)
We have examined the ability of human cell extracts to repair the most frequent DNA adduct caused by the cancer chemotherapeutic agent cis-diamminedichloroplatinum(II). A circular DNA duplex with an intrastrand d(GpG) crosslink positioned at a specific site was synthesized. Human cell extracts were unable to induce repair synthesis in a 29-base-pair region encompassing the adduct or in adjacent regions. The same extracts could repair a single defined 2-acetylaminofluorene lesion in a similar location. When molecules containing the platinum adduct were cleaved by Escherichia coli UvrABC enzyme, human cell extracts could perform repair synthesis at the damaged site, suggesting that human enzymes fail to make incisions near the d(GpG) crosslink but can complete repair once incisions are made. This result indicates that most repair synthesis in DNA damaged with multiple cis-diamminedichloroplatinum(II) adducts takes place at lesions other than the predominant d(GpG) crosslink. These data support the idea that the clinical effectiveness of cis-diamminedichloroplatinum(II) may be explained by the inefficient repair of the major DNA adduct caused by this drug.